THE RELATIONSHIP OF SELECTED NEAR FOREST FARMERS’ CHARACTERISTICS AND THEIR PARTICIPATIONS IN FOREST CONSERVATION AT PARUNG PANJANG, BOGOR - Yayuk Siswiyanti; Basita Ginting S. (Jurnal Penyuluhan, 2006)
Near forest village residents was one of the main forest share holders. So, they should be involved in various forest conservation efforts. Their involvements not only in activities to keep out people from illegal cutting of the forest trees or to put off forest fire, but also in replanting the forest and in other conservation activities. To improve these people welfare, a study on the villagers’ participation in forest conservation was needed. In this conjunction, the objectives of this study were: (1) to determine the villagers’ distributions on their selected characteristics, (2) to identify the villagers’ participation in the forest conservation, and (3) to determine the extent of relationships amongst the villagers’ characteristics and their participations in forest conservation. The population of the study was the residents of nine near forest villages in Parung Panjang sub-district, District of Bogor. The sample was 115 residents taken randomly from the population in those villages. In conjunction with this, this study was designed as a descriptive-correlation research. The independent variables were the villagers’ characteristics and some supporting factors; whereas the dependent variable was the villagers’ participations in the forest conservation. Data were collected through interviews with the villagers in February through April 2006. Descriptive statistic procedure was used to analyze the obtained data. The research findings pointed out that: (1) most of respondents involved in the study were in the older age category, of the Sundanese ethnic, low in education, had never received any training in forest conservation, low in forest conservation knowledge, mostly worked as up-land farmers for five hours daily, and had also low income, (2) their participations in planning, implementing, and evaluating forest conservation as well as in using the forest products were low, and (3) the extents of relationship amongst their characteristics included some supporting factors and their participations in forest conservation were either low or negligible.